The Role of Price, E-Wom, and Store Atmosphere in Taking Purchase Decisions at Coffee Shops in the Digital Age - Wahyu Eko Setianingsih (Agregat: Jurnal Ekonomi dan Bisnis, 2022)
The millennial lifestyle today is visiting cafes to hang out with friends. This makes the cafe business mushrooming in the Jember area. Researchers are interested in conducting this research because of a shift in consumer behavior in seeking information about the products or services used. The purpose of this study was to determine the effect of price, e-wom, and store atmosphere on purchasing decisions at a coffee shop. The population used is visitors to the coffee shop during the study period. The sampling technique used was non-probability sampling with purposive sampling. The statistical tool used to solve the research problem is multiple linear regression accompanied by classical assumption test to ensure that the data is free from bias, accurate in estimation, and consistent. The results of multiple linear regression are the price variable has a significant effect with a value of 0.021 and the e-wom variable is significant with a value of 0.002. While the store atmosphere variable has no effect on purchasing decisions.